Characterization of regulatory T cells in patients with dermatomyositis - Antiga, Emiliano; Kretz, C. C.; Klembt, R.; Massi, D.; Ruland, V.; Stumpf, C.; Baroni, G.; Hartmann, Martin; Hartschuh, Wolfgang; Volpi, W.; Del Bianco, E.; Enk, Alexander; et al. (Journal of autoimmunity, 2010)
The purpose of this study was to characterize regulatory T cells (Treg) in skin lesions and peripheral blood from patients with dermatomyositis (DM) and to determine the serum levels of regulatory cytokines in the disease. In skin biopsy specimens from patients with DM, immunohistochemistry was performed for CD4+, CD25+, forkhead/winged helix transcription factor (FoxP3)+, transforming growth factor (TGF)-β+ and interleukin (IL)-10+ cells. Additionally, we defined the number of Treg subpopulations in peripheral blood by flow cytometry using monoclonal antibodies against CD4, CD25, FoxP3, CD45RO, CD95, CCR4 and CLA. The levels of TGF-β and IL-10 were also determined in serum samples from patients with DM by enzyme-linked immunosorbent assays. Controls included patients with cutaneous lupus erythematosus, psoriasis and atopic dermatitis (AD) as well as healthy donors. The frequency of FoxP3+ cells was significantly reduced in skin lesions from patients with DM (p < 0.001) compared to psoriasis and AD. Moreover, the number of cells positive for TGF-β was lower in DM than in psoriasis and AD, while IL-10+ cells were significantly reduced only compared to psoriasis. The number of CD4+CD25++FoxP3+ Treg in the peripheral blood of patients with DM was significantly reduced compared to healthy controls (p < 0.05), whereas other cell populations showed no significant differences. Finally, TGF-β and IL-10 serum levels were significantly lower in patients with DM compared to healthy controls (p < 0.05). These data suggest that the depletion of Treg and their main effector cytokines in the skin and the serum of patients with DM may be an important factor in the pathogenesis of the disease.